Analysis of Benefit Considerations for Guarantee Company Upgrading to Tier 4 Colocation Data Center in Indonesia - Ferdata Adhitya Winarno Putra; Jarot S. Suroso (Publikasi Indonesia, 2024)
This research is motivated by the need for the guarantee company to improve the management of the availability of information technology services to all company stakeholders in the guarantee company data centre migration project. The guarantee company is currently collaborating with data centre colocation service providers to support information technology infrastructure needs as a location for placing hyper-converged infrastructure servers. One of the objectives of this study is to provide recommendations to company management regarding improvements related to operational efficiency, increased scalability and capacity, reliability, increased availability, increased security factors, compliance with regulations, and the ability to increase data recovery in the event of a disaster by evaluating and maintained for enterprise data centre migration plans. This research focuses on how the benefits of data centre migration are currently at the highest level, which will be explained in this paper, where the author will provide a systematic and measurable visualisation regarding facts and relationships in carrying out the stages of activity, starting with data collection, analysis, and making suggestions in improving colocation data services in the area of the country of Indonesia.